Salvia miltiorrhiza Bge. (Danshen) in the Treating Non-alcoholic Fatty Liver Disease Based on the Regulator of Metabolic Targets - Liu, Jie; Shi, Yun; Peng, Daiyin; Wang, Lei; Yu, Nianjun; Wang, Guokai; Chen, Weidong (Frontiers in Cardiovascular Medicine, 2022)
Non-alcoholic fatty liver disease (NAFLD) is rapidly prevalent due to its strong association with increased metabolic syndrome such as cardio- and cerebrovascular disorders and diabetes. Few drugs can meet the growing disease burden of NAFLD. Salvia miltiorrhiza Bge. (Danshen) have been used for over 2000 years in clinical trials to treat NAFLD and metabolic syndrome disease without clarified defined mechanisms. Metabolic targets restored metabolic homeostasis in patients with NAFLD and improved steatosis by reducing the delivery of metabolic substrates to liver as a promising way. Here we systematic review evidence showing that Danshen against NAFLD through diverse and crossing mechanisms based on metabolic targets. A synopsis of the phytochemistry and pharmacokinetic of Danshen and the mechanisms of metabolic targets regulating the progression of NAFLD is initially provided, followed by the pharmacological activities of Danshen in the management NAFLD. And then, the possible mechanisms of Danshen in the management of NAFLD based on metabolic targets are elucidated. Specifically, the metabolic targets c-Jun N-terminal kinases (JNK), sterol regulatory element-binding protein-1c (SREBP-1c), nuclear translocation carbohydrate response element–binding protein (ChREBP) related with lipid metabolism pathway, and peroxisome proliferator-activated receptors (PPARs), cytochrome P450 (CYP) and the others associated with pleiotropic metabolism will be discussed. Finally, providing a critical assessment of the preclinic and clinic model and the molecular mechanism in NAFLD.